Associations between fibroblast growth factor 23 and cardiovascular disease in children and adolescents: a systematic review and meta-analysis - Na, Jia; Zhen, Zhen; Yu, Wen; Chen, Xi; Yu, Xia; Xiao, Yanyan; Yuan, Yue (Frontiers in Pediatrics, 2026)
ObjectiveOver the previous decade, fibroblast growth factor 23 (FGF23) has been identified as a key biomarker in the context of cardiovascular diseases(CVD). The primary goal of this investigation was to determine the association between FGF23 and the susceptibility to CVD among children and adolescents.MethodsWe performed an electronic search of the Cochrane Library, PubMed, Web of Science, and Embase databases, covering the period from their inception until August 4, 2022. The random effects model was applied. Additionally, we conducted stratified analyses and performed a sensitivity analysis as part of our further investigation.ResultsA total of 11 studies involving 1,428 participants, including 366 individuals with cardiovascular disease and 1,062 control subjects, were included in the analysis. Children and adolescents with cardiovascular disease exhibited significantly higher serum FGF-23 levels compared to the control group [standardized mean difference [SMD] = 1.28, 95% confidence interval [CI] 0.53–2.03; I2 = 93.0%], as determined using a random-effects model. In categorical analyses across six studies, the pooled odds ratio did not demonstrate a statistically significant association with disease risk [odds ratio (OR) = 1.64, 95% CI 0.86–3.12; I2 = 100.0%]. Meta-regression analysis, accounting for variables such as type of cardiovascular disease, assay type, chronic kidney disease (CKD) status, and CKD stage, yielded a restricted maximum likelihood (REML) estimate of (τ2 = 0.2321) for the SMD outcome, indicating residual heterogeneity (I2_res ≈ 70.3%) and an adjusted R2 of 83.6%. The joint test for covariates was not statistically significant (Knapp–Hartung corrected Prob > F = 0.3165). For the categorical outcome, the meta-regression analysis produced a boundary estimate (τ2 = 0) with I2_res = 0% and a non-significant joint test (Prob > F = 0.3479); however, these findings are likely influenced by the limited number of studies and restricted degrees of freedom.ConclusionSerum FGF-23 levels are elevated in pediatric populations with cardiovascular disease, but study-specific thresholds have not shown a clear independent association with risk. The variability in findings, reliance on observational study designs, and differences in assay methods contribute to the uncertainty about its prognostic value. Therefore, standardized prospective studies reporting on renal function and mineral metabolism markers are needed.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023480899, PROSPERO CRD42023480899.